Pengaruh Muslim-friendly service design dan memorable experience terhadap loyalitas wisatawan melalui community engagement - Natasya Putri Syahira; Bethani Suryawardani; Alma Syifa (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2026)
This research is motivated by the declining loyalty of Muslim tourists to urban halal tourism destinations despite the increasing number of visits. In addition, the influence of Muslim-Friendly Service Design on loyalty still shows inconsistent results and the role of Muslim Community Engagement as a mediating variable is still limited research. This study aims to analyze the influence of Muslim-Friendly Service Design and memorable experience on Muslim tourist loyalty through Muslim Community Engagement in the Trans Studio Bandung Integrated Area. The study used a quantitative approach with a survey method of 150 respondents and was analyzed using SEM-PLS. The results showed that memorable experience and Muslim Community Engagement have a significant positive effect on Muslim tourist loyalty, while Muslim-Friendly Service Design has no direct effect on loyalty, but has a significant effect on Muslim Community Engagement. These findings indicate that memorable tourism experiences and community involvement play an important role in strengthening Muslim tourist loyalty.